2020
DOI: 10.2147/opth.s247910
|View full text |Cite
|
Sign up to set email alerts
|

<p>iStent Trabecular Microbypass Stent Implantation with Phacoemulsification in Patients with Open-Angle Glaucoma: 6-Year Outcomes</p>

Abstract: Purpose: To investigate the long-term safety and efficacy of an iStent trabecular microbypass stent in combination with cataract surgery in eyes with primary open-angle glaucoma (POAG). Setting: Private practice; Sioux Falls, South Dakota. Design: Retrospective, consecutive case series. Methods: This case series included eyes implanted with a single trabecular microbypass stent in combination with phacoemulsification in patients with mild to severe POAG. Data were collected preoperatively and at day 1, week 1,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 33 publications
2
27
0
Order By: Relevance
“…This trend also is widely recognized in glaucomatous eyes undergoing combined phacoemulsification and glaucoma procedures, 50,51 and specifically in eyes undergoing iStent or iStent inject implantation either with or without phacoemulsification. [15][16][17][18]26,27 In contrast to the predominant consensus in the literature, four recent non-controlled, non-randomized studies have suggested that success rates are higher in eyes with lower, rather than higher, disease burden: for example, in eyes with lower baseline IOP 44,52 or lower IOP during the first postoperative month; 45 lower number of preoperative medications; 44,45,52 or lower glaucoma severity according to VF MD. 45,53 However, attention must be paid to how these studies defined postoperative success; specifically, none of the studies' success criteria were adjusted for patients' preoperative IOP/medication burden or individual goals for surgery.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…This trend also is widely recognized in glaucomatous eyes undergoing combined phacoemulsification and glaucoma procedures, 50,51 and specifically in eyes undergoing iStent or iStent inject implantation either with or without phacoemulsification. [15][16][17][18]26,27 In contrast to the predominant consensus in the literature, four recent non-controlled, non-randomized studies have suggested that success rates are higher in eyes with lower, rather than higher, disease burden: for example, in eyes with lower baseline IOP 44,52 or lower IOP during the first postoperative month; 45 lower number of preoperative medications; 44,45,52 or lower glaucoma severity according to VF MD. 45,53 However, attention must be paid to how these studies defined postoperative success; specifically, none of the studies' success criteria were adjusted for patients' preoperative IOP/medication burden or individual goals for surgery.…”
Section: Discussionmentioning
confidence: 94%
“…With up to 7 years of postoperative follow-up, iStent studies have often focused on patients with mild to moderate POAG undergoing cataract surgery, but an increasing number of studies have assessed iStent for different glaucoma types (eg, pseudoexfoliative, angle-closure, pigmentary), more advanced severity, standalone cases, and in combination with other procedures or stents. [11][12][13][14][15][16][17][18][19][20][21][22][23] The more recent iStent inject ® Trabecular Micro-Bypass (CE Mark 2010, FDA approval 2018) contains two stents that create two patent bypasses through the diseased trabecular meshwork. This device has been studied both with and without concomitant cataract extraction, and in studies with up to 5 years of follow-up.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The degree of postoperative IOP reduction also was greater in eyes with higher preoperative IOP, as has been shown previously. 10 , 12–14 , 21 Importantly, the outcomes in both groups were achieved in consecutive (all-comer) patients in the context of the surgeon’s clinical practice, with the patient population including different glaucoma subtypes and severities. The subgroup analysis of secondary glaucoma cases (PXG and PG), although limited in size, revealed favourable IOP and medication reductions, consistent with previously published larger studies of the iStent specifically in these populations.…”
Section: Discussionmentioning
confidence: 99%
“…MIGS procedures are predicated on safety, can be combined with cataract surgery, as well as other MIGS procedures [ 8 , 9 ] without interfering with future surgical intervention [ 10 , 11 ]. Although the iStent has been extensively studied in patients with primary open-angle glaucoma (POAG) in the short-term [ 12 15 ] there are few studies reporting long-term data in these patients [ 16 , 17 ]. This study aims to evaluate the real-world long-term (5-year) safety and efficacy of single iStent (G1) in combination with micro-incision cataract surgery in patients with moderately advanced POAG.…”
Section: Introductionmentioning
confidence: 99%